STRESS AND COPING STRESS ON MOTORCYCLE DRIVER - Muhammad Jumadil Akbar; Dona Eka Putri (Jurnal Psikologi, 2007)
The imbalance increasing number of motorcycle every year compared to the increasing street development causing traffic jam. The traffic jam also cause stress on motorcycle driver. The aim of this study is to know the stress and the coping stress on motorcycle driver, with one research subject which is a man who usually drive motorcycle every day. The factors that can cause stress are physic stressor; such as weather and traffic jam, social stressor; such as busy hours, crowded streets and reckless drivers. The psychological symptomps are exhausted physic and easy to get angry or mad on the street. The subject uses emotion-focused coping and problem-focused coping to handle those conditions.Key words: stress, coping stress, motorcycle driver